Square Transposition Method with Adaptive Key Flexibility and Strong Diffusion Performance - Magdalena Ariance Ineke Pakereng; Alz Danny Wowor; Yos Richard Beeh; Felix David; Erwien Christianto; Vincent Exelcio Susanto; Claudio Canavaro (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2025)
The Square Transposition method has notable potential in enhancing diffusion within block encryption systems; however, its application is typically limited to perfect square key lengths. The objective of this study is to reconstruct the method to accommodate non-square key lengths by utilizing two square matrices. To assess the effectiveness of the proposed approach, the method of this study uses a comparative analysis conducted against the transposition structures found in DES and AES algorithms, both of which are cryptographic standards established by NIST. The comparison is strictly limited to the transposition component, excluding other components of the full encryption framework. The evaluation involves Monobit, Block Bit, and Run Tests, along with Pearson correlation analysis between plaintext and ciphertext. Tests are conducted on 16 input variations across three key sizes: 128-bit, 256-bit, and 512-bit. The results of this study show that the proposed method achieves lower correlation values (r = 0.02) compared to DES (r = 0.07) and AES (r = 0.05). The conclusion of this study is that these findings indicate the approach offers improved key flexibility and diffusion capability, making it a promising transposition component for block cipher encryption systems. This reconstruction contributes a novel transposition structure that is compatible with non-square key sizes, thereby enhancing both diffusion strength and adaptability in modern cryptographic applications.